Effects of proton pump inhibitor (PPI) use on migraine – a critical review - Viktoria Tischler-Strasser; Irma Burdiladze; Goncalo Cabral; Esme Ekizoglu; Olga Grodzka; Keshet Pardo; Patryk Sochan; Laura Zaunandra; Antoinette MaassenVanDenBrink; Christian Lampl; on behalf of the European Headache Federation School of Advanced Studies (EHF-SAS) (The Journal of Headache and Pain)
Abstract Background Proton pump inhibitor (PPI) drugs are widely used and are among the most significant achievements of modern pharmacology. Their primary purpose is treating and preventing gastric acid-related disorders. Migraine and PPI intake are prevalent, and many people are affected by both. In the last few years, a potential link between PPI intake and the development of headaches—especially migraine–has come to increased attention. In this review, we critically examine the scientific data concerning the co-occurrence of these two entities. Findings There seems to be a possible link between the use of PPIs and the occurrence of headache, especially migraine, suggesting a pathophysiological connection on several levels. Moreover, PPI use is only partially without side effects, even if these may not occur immediately. Whether the relation is causative or merely co-existential is currently not yet clear. The influence of genetics, environment, gut microbiome, medication intake and evolution of headache is multidirectional. Conclusion A relation between the prevalence of migraine and the use of PPIs on a population and personal level seems likely. Although PPIs have many advantages, they should be prescribed with caution, especially in patients who suffer from headaches and migraine. In this narrative review, we aim to critically evaluate existing data and offer a potential approach to accurately identify any connections and interactions, leading to a better understanding of how these conditions may influence each other.